A heat- and mass-integrated design of hydrothermal liquefaction process co-located with a Kraft pulp mill. (15th December 2019) - Ong, Benjamin H.Y.; Walmsley, Timothy G.; Atkins, Martin J.; Varbanov, Petar S.; Walmsley, Michael R.W.
Abstract: This paper aims to establish a new standard process for heat and mass integration of hydrothermal liquefaction, co-located with an existing Kraft pulp mill, to produce bio-crude. Hydrothermal liquefaction is an energy-intensive process that operates at high temperature and pressure and produces a biocrude similar to conventional crude oil. The key advantages of installing hydrothermal liquefaction in proximity with a Kraft Mills enables the use of black liquor as a feed to hydrothermal liquefaction, asset repurposing and optimisation, as well as supply chain and logistics integration. This work follows a design process to increase the energy efficiency of the hydrothermal liquefaction process by using an iterative mass and heat integration procedure to optimise mass and energy flows and assets of the hydrothermal liquefaction process. The method uses process simulation tools, Pinch Analysis, heat exchanger network design tool, and the understanding of the process constraints to develop a heat exchanger network for the hydrothermal liquefaction process with maximum energy recovery, minimum number of units and enhanced mass integration. The number of heat exchangers in the network reduced from 14 to 7 when the proposed method was applied. Substituting bio-crude from the new integration hydrothermal liquefaction process for conventional fuels has the potential to decarbonise transport fuels by 11.3 kg CO2 -e/GJ of fuel. Highlights: Developed an iterative procedure to optimise process mass and energy flows. Applied the new procedure to an emerging technology, hydrothermal liquefaction. Identified critical processing constraints to ensure practical energy recovery design. Reduced heat exchanger units in final design by 50% and maximised energy recovery.